2014
DOI: 10.1073/pnas.1323845111
|View full text |Cite
|
Sign up to set email alerts
|

Polyclonal type II natural killer T cells require PLZF and SAP for their development and contribute to CpG-mediated antitumor response

Abstract: CD1d-restricted natural killer T (NKT) cells are innate-like T cells with potent immunomodulatory function via rapid production of both Th1 and Th2 cytokines. NKT cells comprise well-characterized type I NKT cells, which can be detected by α-galactosylceramide-loaded CD1d tetramers, and less-studied type II NKT cells, which do not recognize α-galactosylceramide. Here we characterized type II NKT cells on a polyclonal level by using a Jα18-deficient IL-4 reporter mouse model. This model allows us to track type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
84
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 55 publications
(50 reference statements)
5
84
0
Order By: Relevance
“…21 However, recent studies using sulfatide-reactive type II NKT cell hybridoma XV19 and Ja18-deficient IL-4 reporter mice report recognition of b-GlcCer (12:0 and 24:1) by murine type II NKT cells. 24,26 In contrast to initial findings from Brennan et al, our data pointed to b-glucosylceramide as a ligand for type II as opposed to type I NKT cells. Recent studies have attributed Brennan's initial findings to a contaminating minor lipid species, consistent with endogenous a-linked glucosylceramide.…”
Section: Discussionmentioning
(Expert classified)
See 1 more Smart Citation
“…21 However, recent studies using sulfatide-reactive type II NKT cell hybridoma XV19 and Ja18-deficient IL-4 reporter mice report recognition of b-GlcCer (12:0 and 24:1) by murine type II NKT cells. 24,26 In contrast to initial findings from Brennan et al, our data pointed to b-glucosylceramide as a ligand for type II as opposed to type I NKT cells. Recent studies have attributed Brennan's initial findings to a contaminating minor lipid species, consistent with endogenous a-linked glucosylceramide.…”
Section: Discussionmentioning
(Expert classified)
“…In addition to its well-documented role in type I NKT cells, PLZF was recently implicated in the differentiation of type II NKT cells as well. 26,57 Crosstalk between type I and II NKT cells is increasingly implicated in the regulation of immunity to pathogens, tumors, and autoimmunity. 5,7,50,58 The mechanism underlying the crosstalk between NKT subsets requires further study and may be more prominent with specific ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike both types of CD1d-restricted NKT cells, which are activated by b-linked glycosphingolipids, HJ1 T cells were not activated by sphingolipids. 22,[41][42][43] A recent study also suggests that mammalian a-linked glycosphingolipids can activate type I NKT cells. 44 Although ether-linked forms of pLPE and lysophaphatidic have been implicated in the selection of type I NKT cells, nothing is known about the selecting self-lipids for type II NKT cells and group 1 CD1-reactive T cells.…”
Section: Discussionmentioning
confidence: 98%
“…[18][19][20][21] Interestingly, a previous study showed that the immunosuppressive effect of type II NKT cells is reversed in the presence of CpG oligodeoxynucleotides (ODN), a TLR 9 agonist, leading to an increased ratio of IFNg to IL-13 production. 22 These data suggested that CD1d-restricted NKT cells could potentially be used in adoptive immunotherapy to treat tumors.…”
Section: Introductionmentioning
confidence: 96%
“…While it has become clear that TLR signalling events upregulate presentation of endogenous lipids, which can then activate iNKT cells [17,18], the identity of such self-lipids capable of modulating iNKT cell auto-reactivity remains elusive (reviewed in [23]). In contrast to iNKT cells, due to limited reagents for type II NKT cell identification, the antigenic specificity of type II NKT cells is only just beginning to emerge; reactivity has been observed with sulfatide [24], lysophospholipids [25,26], and more recently with b-D-glucopyranosylceramide (b-GlcCer) and its deacylated product, glucosylsphingosine (LGL1), which are presented in Gaucher disease patients [27][28][29].…”
Section: Introductionmentioning
confidence: 99%